2019
DOI: 10.1186/s12885-019-5832-9
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of YAP inhibits growth in Hep-2 laryngeal cancer cells via epithelial-mesenchymal transition and the Wnt/β-catenin pathway

Abstract: Background Yes-associated protein (YAP) plays a crucial role in tumour development and it is the main effector of the Hippo signalling pathway. However, the mechanism underlying YAP downregulation in laryngeal cancer is still unclear. In our previous study, we found that YAP, compared with adjacent tissues, was expressed higher in laryngeal cancer and was also closely associated with histological differentiation, TNM stage and poor prognosis. Methods In this study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, YAP was reported to contribute to tumor initiation, progression and metastasis ( 37 ). Tang et al ( 38 ) demonstrated that the expression of β-catenin was markedly reduced after YAP downregulation in laryngeal cancer cells. Wang et al ( 39 ) also reported that P-YAP contributed to the degradation of β-catenin in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, YAP was reported to contribute to tumor initiation, progression and metastasis ( 37 ). Tang et al ( 38 ) demonstrated that the expression of β-catenin was markedly reduced after YAP downregulation in laryngeal cancer cells. Wang et al ( 39 ) also reported that P-YAP contributed to the degradation of β-catenin in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/ β-catenin downregulation is helpful to reduce LCA cell malignant episodes. 39 Taken together, miR-139-3p overexpression curtails LCA cell growth and promotes cancer cell apoptosis via the KDM5B-mediated SOX2/Wnt/βcatenin axis.…”
Section: Dovepressmentioning
confidence: 97%
“…In 3T3-L1 cells, disruption of the YAP/TAZ and TEAD interaction by VP treatment significantly reduced DKK1 mRNA, and knockdown of TEAD reduced DKK1 levels 39 . In Hep-2 cells, the expression of DKK1 was significantly decreased after YAP downregulation 40 . There may indeed be a feedback loop.…”
Section: Discussionmentioning
confidence: 96%